Migration policy and national minorities in the Republic of Lithuania: lessons for Ukraine - Shulga, Taisiya (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa, UAM, 2020)
The purpose of the article is to determine the factors that influenced the process of the development and implementation of Lithuania’s foreign and domestic policies in the field of migration within the framework of the EU rules (dispositive and imperative) and identify those factors that may have a similar effect on the stability of migration processes in Ukraine with regard to its accession to the EU. The task is to determine the problems (negative preconditions and consequences) of the migration sector based on the analysis of more than a decade of experience of Lithuania as an EU member and the influence of the latest European crisis. Lithuania’s strategies with regard to the following issues are relevant to Ukraine’s European integration aspirations: the migration crisis in the EU, in terms of overcoming it through a “relocation plan;” and the integration of the national minorities of Lithuania, including the Roma minority, into the country’s civil society. Furthermore, some of Lithuania’s efforts actively support Ukraine’s European integration aspirations, such as the attempt to model how current problems can be predicted and resolved by Ukraine if it acquires EU membership, on the basis of Lithuania’s experience, which has relevance for Ukraine due to the fact that Lithuania and Ukraine – along Poland and other countries – inherited the Soviet system of government, and because of their similar mentality and current bilateral relations. After the Ukrainian crisis in 2014, and the subsequent EU migration crisis in 2015, Lithuania reviewed its national policy priorities taking into account that its state boundary is the part of the EU boundary, without any “buffer zone.”

Celem artykułu jest określenie czynników, które wpłynęły na proces opracowywania i realizacji litewskiej polityki zagranicznej i krajowej w zakresie migracji w ramach przepisów UE (dyspozycyjnych i imperatywnych) oraz wskazanie tych czynników, które mogą mieć podobny wpływ na stabilność procesów migracyjnych na Ukrainie w związku z jej przystąpieniem do UE. Zadanie polega na określeniu problemów (negatywnych uwarunkowań i konsekwencji) sektora migracji w oparciu o analizę ponad dekady doświadczeń Litwy jako członka UE oraz wpływu ostatniego kryzysu europejskiego. Strategie Litwy w odniesieniu do następujących zagadnień są istotne dla aspiracji Ukrainy w zakresie integracji europejskiej: kryzys migracyjny w UE, w zakresie przezwyciężenia go poprzez „plan relokacji”; oraz integracja mniejszości narodowych Litwy, w tym mniejszości romskiej, ze społeczeństwem obywatelskim kraju. Ponadto, niektóre wysiłki Litwy aktywnie wspierają aspiracje Ukrainy w zakresie integracji europejskiej, takie jak próba modelowania, w jaki sposób Ukraina może przewidywać i rozwiązywać bieżące problemy w przypadku uzyskania członkostwa w UE, na podstawie doświadczeń Litwy, co ma znaczenie dla Ukrainy ze względu na fakt, że Litwa i Ukraina – wraz z Polską i innymi krajami – odziedziczyły sowiecki system rządów, a także ze względu na ich podobną mentalność i obecne stosunki dwustronne. Po kryzysie ukraińskim w 2014 roku, a następnie kryzysie migracyjnym UE w 2015 roku, Litwa zrewidowała swoje priorytety polityki krajowej, biorąc pod uwagę, że jej granica państwowa jest częścią granicy UE, bez żadnej „strefy buforowej”.
Polityka migracyjna i mniejszości narodowe w Republice Litewskiej: lekcje dla Ukrainy
Keywords: Republic of Lithuania; migration policy; EU migration crisis; national minorities; immigration; state language development; Republika Litewska; polityka migracyjna; kryzys migracyjny UE; mniejszości narodowe; imigracja; rozwój języka państwowego